Legislative framework governing labour broking in South Africa - Kutumela, Malose Titus (University of Limpopo (Turfloop Campus), 2013)
The study will analyse section 198 of the Labour Relations Act of 66 of 1995. The section is the founding provision of labour broking and also provides for joint and several liabilities between the client and the broker in instances of infringement of this section. The utilization of labour brokers in South Africa has sparked debates between various stake-holders, with the other side arguing that labour broking should be banned it diminishes the rights of employees. In order to resolve the challenge relating to labour broking the study will make comparative analysis with the Namibian jurisprudence. The study takes full cognize of legislative framework governing labour broking and determines whether the available legislation provide full protection of labour rights. Through case law the study will highlight the constitutional challenges o labour broking in South Africa and challenges faced by employees employees employed through labour broking. The study concludes tht the regulation of labour broking is appropriate as the industry creates employment nd thus alleviates poverty and that the total ban labour broking in South Africa would be detrimental to those who seek employment without the necessary skills and qualifications.
Thesis (LLM (Labour law)) --University of Limpopo, 2013
Keywords: Labour broking; Labour laws; Employment agencies; Labour Relations Act; 344.01128; Labor laws; Employment agencies; Industrial relations - South Africa